How to read and why - Bloom, Harold. 4 0 16; 5 (New York : Simon & Schuster, 2001)
Examines short stories, poems, plays, and novels by literary greats such as Shakespeare, Keats, Austen, Whitman, and Hemingway to show twenty-first-century readers the pleasure and power of reading.
Originally published: New York : Scribner, 2000.
Library Journal;Publisher's Weekly;Booklist
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Appreciation.;Study and teaching.;History and criticism.;Study and teaching.;History and criticism. -- Reading.;Literature;Literature, Modern;Literature, Modern;Books and reading.;Literature.;Modernism in literature;Modernism in literature; 20; 2